Tinjauan Semiotika dan Estetika Poster Film Flow (2024) - Fadhillah Fahriansyah; Onang Murtiyoso (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to uncover the mechanisms of visual communication in non-verbal animated film posters through semiotic and aesthetic analysis. The research object selected is the poster for the film Flow (2024), a unique work characterized by the absence of verbal communication in its narrative, thereby placing the entire burden of message delivery on visual elements. The method employed is descriptive qualitative with a two-stage semiotic significance approach by Roland Barthes, reinforced by theories of color psychology and visual composition. The results indicate that the Flow (2024) poster constructs meanings of resilience and non-human agency through the use of a